Food Security and Global Environmental Change:: an Analysis in the Context of Brazilian Society - Nolasco, Camille Lanzarotti; Lahsen, Myanna; Ometto, Jean Pierre Henry Balbaud (Sustainability in Debate, 2016)
Agriculture is closely related to global environment change, being part of both its causes and consequences. Global environmental change can increase the vulnerability of society’s food security. From a holistic point of view of the food system, this texts seeks to contextualize the link between food security and global environmental change by means of a literature review. The study points out the risks posed to Brazil’s food security and its vulnerability, along with the mitigation and adaptation measures needed to overcome the problem. The authors highlight challenges for policy making and scientific research on global environmental change and food security in Brazil.